The effect of a novel impact management strategy on maximum principal strain for reconstructions of American football concussive events. (December 2019) - Taylor, Karen; Post, Andrew; Hoshizaki, Thomas Blaine; Gilchrist, Michael D
The purpose of this study was to test the effectiveness of a helmet to reduce maximum principal strain by decoupling the head–helmet interface in reconstructions of head-to-head concussive impacts in American football. The primary goal of the American football helmet has been protection of players against skull fractures and other traumatic brain injuries. The modern-day helmet has evolved and been designed to mitigate traumatic brain injury, but it does not offer optimized protection against concussive injury. Studies to determine the influence of decoupling strategies on changes to brain motion and the resulting influence on maximum principal strain, a metric associated with concussive injury, have not yet been examined under concussive impact conditions. In this study, 19 helmet-to-helmet concussive events from professional American football were reconstructed using a pneumatically driven linear impactor to determine the components (resultant and dominant) of linear and rotational acceleration. The University of College Dublin Brain Trauma Model was used to determine maximum principal strain values. A prototype helmet with a decoupling liner strategy was shown to significantly reduce maximum principal strain in seven of the head-to-head concussive impact reconstructions. In each case, the prototype helmet significantly reduced the dominant coordinate component of rotational acceleration. The results of this study indicate the potential of a helmet liner decoupling system in reducing maximum principal strain for reconstructions of concussive events in American football.